Exploring the factors affecting organizational effectiveness in T.A.G Marine Sdn. Bhd. (TMSB) / Nur Amira Zulkefli - Zulkefli, Nur Amira (Faculty of Business Management, 2017)
Organizational effectiveness is an important topic to be studied either by researchers or businessmen. Some organizations have several factors affecting the effectiveness of their company. This study aims to explore the factors that affect organizational effectiveness in T.A.G. Marine Sdn. Bhd. (TMSB). The researcher chose to use four independent variables that may affect organizational effectiveness which are leadership, employee engagement, organizational capabilities and organizational communication. Questionnaires were distributed to 75 employees as the appropriate sample size is 70. This is to be safe when eliminating foul questionnaires from the respondents (if any). The researcher chose simple random sampling techniques for this study. All the quantitative data obtained from this research study were analyzed by the Statistical Package for the Social Sciences Software (SPSS) version 20. The results from this study including the conclusions and recommendations will help future researchers to explore the factors of organizational effectiveness in more detailed and accuracy.